Perlindungan Hukum Bagi Kreditur dalam Hal Terjadi Wanprestasi pada Program Kredit Angsuran Sistem Fidusia di PT Pegadaian Cabang Denpasar - I Nyoman Putu Budiartha; Putu Berliana Prema Swari; Desak Gde Dwi Arini (Warmadewa Press, 2022)
This study aims to analyze and describe the process of providing credit with a creative program and a form of legal protection if the debtor defaults on the creation program at PT Pegadaian Denpasar. Pegadaian was born as the foundation of the high-quality will of the ruler of a country to help many people who need funding solutions. One of the results of PT Pegadaian is creation, the result is a pawn system which is also intended for all of the lenders, both for consumptive and productive needs. The type of research used in this research is empirical legal research. Based on the results of the study, it can be seen that the high rate of default in 2021 occurred at PT Pegadaian Denpasar branch of 205 customers who defaulted as many as 69 people or 33.69%. This has legal implications. Meanwhile, legal protection for creditors refers to the Civil Code, legal protection for parties who have debts in credit agreements and fiduciary dependents very needed to think that the object made mortgage is on the side of the debtor.